PHEs, Environment and Human Health 2014
DOI: 10.1007/978-94-017-8965-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Harmful Elements in Urban Soils

Abstract: Throughout the human history, the anthropic activity inevitably leads to a legacy of increased PHE concentration in the environment. Nowadays the urban environment can be considered the main habitat for humans. Therefore, the acknowledgment and the understanding of the impact of PHEs in urban soils and dusts is imperative in order to develop a plan for the sustainable management of urban areas, which should limit this impact on human and environmental health. A historical background regarding urban soil contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 160 publications
0
2
0
Order By: Relevance
“…In this study, the CR of Cr was slightly higher than that of As (Table 4). Studies have shown that long-term exposure to low-dose concentrations of Cr will have toxic and carcinogenic effects on human body (Angelone & Udovic, 2014). Wuwei farmland soil was more polluted by Cr (Figure 2a), and the SF value of Cr was higher under the ingestion pathway, so Cr had higher CR for adults and children (Table 4).…”
Section: 2mentioning
confidence: 99%
“…In this study, the CR of Cr was slightly higher than that of As (Table 4). Studies have shown that long-term exposure to low-dose concentrations of Cr will have toxic and carcinogenic effects on human body (Angelone & Udovic, 2014). Wuwei farmland soil was more polluted by Cr (Figure 2a), and the SF value of Cr was higher under the ingestion pathway, so Cr had higher CR for adults and children (Table 4).…”
Section: 2mentioning
confidence: 99%
“…Während einige Grundlagenuntersuchungen zu städtischen Böden vorliegen (Grenzius 1987, Hiller & Meuser 1998, ist deren Bezug zur Gesundheit in Städten bisher nur wenig beleuchtet worden (Angelone & Udovic 2014). Positive Auswirkungen könnten hierbei unversiegelte und biologisch aktive Böden im Hinblick auf das Mikroklima, die städtischen Wasser-und Nährstoffkreisläufe und das Naturerleben haben, negative Auswirkungen ergeben sich durch kontaminierte Stadtböden bzw.…”
Section: Bödenunclassified
“…As one of the most important components of the urban ecosystem, soil provides a growing medium, habitat, and nutrients for plants and soil microbes. It also serves as an important sink for urban pollution, helping to absorb, degrade, and reduce levels of pollutants (Sheng et al 2012;Ayrault et al 2013;Rota et al 2013;Angelone and Udovic 2014). Human activities, however, have seriously affected the overall quality of soil and changed its physical and chemical conditions.…”
Section: Introductionmentioning
confidence: 99%